Mobilidade pendular e mercado de trabalho na Região Metropolitana de Belo Horizonte: uma análise a partir dos dados dos censos demográficos - Breno Aloisio Torres Duarte de Pinho (2012)
In the urban sprawl of the cities, the conditions for the dissociation between city of labor and city of residence are created by selective processes of population and economic activities distribution in space. In the case of the Metropolitan Region of Belo Horizonte, the urban expansion was characterized by intra-metropolitan migration, with primary sense core-periphery, and the allocation of part of the economic activities, especially the industrial sector, in peripheral areas. This urban expansion resulted in the formation of metropolitan expansion vectors, which demonstrate commuting patterns characterized by the connection with the metropolitan core. In this research, it will be discussed the formation of metropolitan commuting flows in the context of the metropolization of Belo Horizonte. It examines the changes in the metropolitan labor market and the commuting flows based on data from 1970, 1980, 2000 and 2010 Censuses. The results show that the formation of the major metropolitan commuting flows is associated with the periphery of the population and with the economic expansion of the major industrialized areas of the periphery. Confirming the evidences described in the literature, the end results indicate that intra-metropolitan migrations reinforce commuting flows.